Interaction between the Existing and the New Constructed Tunnels - Nahla M. Salim (Engineering and Technology Journal, 2013)
The effect of construction new tunnel on nearby tunnel was investigated using finite element software program SIGMA/W. Two methods of excavation were used, one using one stage in construction of tunnels and the other using eight stages of excavation. The analysis also carried out to study the effect of nearby tunnel on existing tunnel by varying the pillar width (W), using W equal to 3, 5, 7 and 12 m. The results show that, using stages in construction of tunnel has no significant effect comparing with one stage. The study indicates that there is significant effect of position of new tunnel on the existing tunnel.